Host allometry influences the evolution of parasite host-generalism: theory and meta-analysis. (5th May 2017) - Walker, Josephine G.; Hurford, Amy; Cable, Jo; Ellison, Amy R.; Price, Stephen J.; Cressler, Clayton E.
Abstract : Parasites vary widely in the diversity of hosts they infect: some parasite species are specialists—infecting just a single host species, while others are generalists, capable of infecting many. Understanding the factors that drive parasite host-generalism is of basic biological interest, but also directly relevant to predicting disease emergence in new host species, identifying parasites that are likely to have unidentified additional hosts, and assessing transmission risk. Here, we use mathematical models to investigate how variation in host body size and environmental temperature affect the evolution of parasite host-generalism. We predict that parasites are more likely to evolve a generalist strategy when hosts are large-bodied, when variation in host body size is large, and in cooler environments. We then explore these predictions using a newly updated database of over 20 000 fish–macroparasite associations. Within the database we see some evidence supporting these predictions, but also highlight mismatches between theory and data. By combining these two approaches, we establish a theoretical basis for interpreting empirical data on parasites' host specificity and identify key areas for future work that will help untangle the drivers of parasite host-generalism. This article is part of the themed issue 'Opening the black box: re-examining the ecology and evolution of parasite transmission'.